2001
DOI: 10.1038/sj.bmt.1703273
|View full text |Cite
|
Sign up to set email alerts
|

Flexible bronchoscopy in the diagnosis of pulmonary infiltrates following autologous peripheral stem cell transplantation for advanced breast cancer

Abstract: Summary:Flexible bronchoscopy is an important tool in the diagnosis of pulmonary complications following bone marrow transplantation. However, the value of this procedure in autologous peripheral stem cell transplant (APSCT) recipients with pulmonary complications is not well defined. We retrospectively evaluated the diagnostic yield of 27 consecutive bronchoscopies done on 23 APSCT recipients following high-dose chemotherapy for breast cancer. FB resulted in a positive diagnosis in 16 cases (59%). Broncheoalv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
0
12
0
2
Order By: Relevance
“…The study by Glazer et al 7 showed the highest yield, but this may be explained in part because they did not include any information on their prophylactic antiinfective regimen, they did not document what criteria were used to establish a diagnosis of bacterial pneumonia and they diagnosed idiopathic pneumonia syndrome from histologic features which are not standard. Soubani et al 32 reported an unusually high yield from transbronchial biopsies, but this likely resulted from a retrospective review of only metastatic breast cancer patients who had received autografts conditioned with BCNU and cyclophosphamide, biasing the yield to drug toxicity or recurrent cancer. 33,34 There are a number of limitations to our retrospective study.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Glazer et al 7 showed the highest yield, but this may be explained in part because they did not include any information on their prophylactic antiinfective regimen, they did not document what criteria were used to establish a diagnosis of bacterial pneumonia and they diagnosed idiopathic pneumonia syndrome from histologic features which are not standard. Soubani et al 32 reported an unusually high yield from transbronchial biopsies, but this likely resulted from a retrospective review of only metastatic breast cancer patients who had received autografts conditioned with BCNU and cyclophosphamide, biasing the yield to drug toxicity or recurrent cancer. 33,34 There are a number of limitations to our retrospective study.…”
Section: Discussionmentioning
confidence: 99%
“…(39% auto) Gruson [98] 2000 NR 49% BAL Soubani [59] 2001 Autologous 59% BAL +TBBX Feinstein [60] 2001 Allogeneic 42% BAL + TBBX specific yield for infection in this series was 67% (10 of 15 TTNAs), which was comparable to bronchoscopy. Complications were observed in 18 of 71 patients (25%), with pneumothorax occurring in 14 patients (20%) and 4 patients (6%) requiring chest tube placement.…”
Section: Transthoracic Needle Aspiration (Ttna)mentioning
confidence: 61%
“…Soubani and co-workers reviewed 27 bronchoscopies and transbronchial biopsies (TBBX) in breast cancer patients who underwent HSCT [59]. The most common causes of lung lesions were pulmonary drug toxicity (47%), bacterial infection (17%), and IPA (11%).…”
Section: Fiberoptic Bronchoscopy (Fob)mentioning
confidence: 99%
“…The reported diagnostic yield of BAL in immunocompromised patients, including those with HIV or solid organ transplant, with pulmonary infiltrates ranges widely from 22 to 80%. [5][6][7][8][9] Studies of BAL sensitivity in hematopoietic stem cell transplant (HSCT) patients report yields of 22-65%. 6,7,[9][10][11][12] With respect to the yield of BAL in non-resolving pneumonia one study in the general intensive care unit (ICU) setting, Pereira Gomes reported a 72% yield in 53 patients.…”
mentioning
confidence: 99%
“…[5][6][7][8][9] Studies of BAL sensitivity in hematopoietic stem cell transplant (HSCT) patients report yields of 22-65%. 6,7,[9][10][11][12] With respect to the yield of BAL in non-resolving pneumonia one study in the general intensive care unit (ICU) setting, Pereira Gomes reported a 72% yield in 53 patients. 13 We sought to examine the effect of antimicrobial treatment on BAL results in a large study population of leukemic and bone marrow transplant patients.…”
mentioning
confidence: 99%